Do I Really Feel Your Pain? Comparing the Effects of Observed and Personal Ostracism. (April 2018) - Giesen, Anna; Echterhoff, Gerald
It has been argued that "we feel the pain of others' ostracism as our own". However, it is unknown whether observed ostracism is as distressing as self-experienced ostracism. We conducted two studies to address this lacuna. In Study 1, participants played or observed an online ball-tossing game, in which they or a stranger were ostracized or included by others. In Study 2, participants imagined themselves or someone else being ostracized or included. Across both studies, self-experienced and observed ostracism had the same negative effect on mood. Also, both self-experienced and observed ostracism evoked need threat, but this effect was slightly lower after observed ostracism. In sum, the findings suggest that we do feel the pain of others' ostracism as our own, consistent with the notion that humans are equipped with a system that detects violations of social inclusion norms in the environment.